Cellular Distribution of Canonical and Putative Cannabinoid Receptors in Canine Cervical Dorsal Root Ganglia - Chiocchetti, Roberto; Galiazzo, Giorgia; Tagliavia, Claudio; Stanzani, Agnese; Giancola, Fiorella; Menchetti, Marika; Militerno, Gianfranco; Bernardini, Chiara; Forni, Monica; Mandrioli, Luciana (Frontiers in Veterinary Science, 2019)
Growing evidence indicates cannabinoid receptors as potential therapeutic targets for chronic pain. Consequently, there is an increasing interest in developing cannabinoid receptor agonists for treating human and veterinary pain. To better understand the actions of a drug, it is of paramount importance to know the cellular distribution of its specific receptor(s). The distribution of canonical and putative cannabinoid receptors in the peripheral and central nervous system of dogs is still in its infancy. In order to help fill this anatomical gap, the present ex vivo study has been designed to identify the cellular sites of cannabinoid and cannabinoid-related receptors in canine spinal ganglia. In particular, the cellular distribution of the cannabinoid receptors type 1 and 2 (CB1 and CB2) and putative cannabinoid receptors G protein-coupled receptor 55 (GPR55), nuclear peroxisome proliferator-activated receptor alpha (PPARα), and transient receptor potential vanilloid type 1 (TRPV1) have been immunohistochemically investigated in the C6–C8 cervical ganglia of dogs. About 50% of the neuronal population displayed weak to moderate CB1 receptor and TRPV1 immunoreactivity, while all of them were CB2-positive and nearly 40% also expressed GPR55 immunolabeling. Schwann cells, blood vessel smooth muscle cells, and pericyte-like cells all expressed CB2 receptor immunoreactivity, endothelial cell being also PPARα-positive. All the satellite glial cells (SGCs) displayed bright GPR55 receptor immunoreactivity. In half of the study dogs, SGCs were also PPARα-positive, and limited to older dogs displayed TRPV1 immunoreactivity. The present study may represent a morphological substrate to consider in order to develop therapeutic strategies against chronic pain.